Influence of Relationship Commitment and Trust on Collaborative Behaviour in Supply Chains - Mlaker Kač, Sonja; Gorenak, Irena; Potočan, Vojko (Promet - Traffic&Transportation, 2015)
The paper discusses theoretically and examines empirically the influence of the relationship commitment on collaborative behaviour in supply chains. In today’s unstable business environment companies should collaborate to achieve mutual goals and competitive advantage. Defining relationship commitment and collaboration in supply chains (from social exchange theory point of view) is the basis of the research of this paper. Our aim is to examine the influence of relationship commitment on collaboration in supply chains in Slovenian economy. The qualitative research part discusses if the relationship commitment between partners in supply chain influences the collaborative behaviour between partners and which are the antecedents of relationship commitment. The research is based on a quantitative analysis of the online questionnaire survey made on the Slovenian economy. The research results show strong influence of trust and relationship commitment on collaboration between partners in supply chains.